Nickel-Catalyzed Deuteroalkylation Using Thianthrenium Salts - Zhang, Jie; Shi, Zhuangzhi (Synlett, 2025)
Isotopically labeled compounds are essential in both organic and pharmaceutical chemistry. The standard methods for synthesizing such molecules often involve the use of deuterated building blocks, allowing the incorporation of functional groups and deuterium into the target molecule in one step. In this Synpacts article, we highlight our approach to accessing various a-deuterated alkyl thianthrenium (TT) salts through a pH-dependent hydrogen-isotope-exchange process using D2O as a cheap source of deuterium. Through the in situ formation of isotopically labeled alkyl halides, these TT salts exhibit exceptional compatibility with a range of nickel-catalyzed hydrodeuteroalkylations of nonactivated olefins and with nickel-catalyzed cross-electrophile coupling reactions with alkyl, alkenyl, and (het)aryl bromides. This technique has proven to be invaluable for accessing a range of deuterium-labeled compounds, particularly those of pharmaceutical significance.
Keywords: deuteriation; thianthrenium salts; hydrodeuteroalkylation; nickel catalysis; metallaphotoredox reaction; pharmaceutical chemistry